Different implications of daytime and nighttime heart rate variability on total burden of cerebral small vascular disease in patients with nondisabling ischemic cerebrovascular events - Zhang, Zhixiang; Lv, Yijun; Wang, Qian; Wang, Yan; Zhang, Min; Cao, Yongjun (Frontiers in Cardiovascular Medicine, 2024)
Objective: This study aimed to explore the relationship between total burden of cerebral small vessel disease (CSVD) and daytime and nighttime heart rate variability (HRV) parameters. Method: Consecutive patients with nondisabling ischemic cerebrovascular events were recruited from the cerebrovascular disease clinic of Changzhou Second People’s Hospital between January 2022 and June 2023. A total of 144 enrolled participants were divided into a mild CSVD group (74 patients) and a moderate-to-severe CSVD group (70 patients) based on total burden of CSVD. Various HRV parameters measured during 24-h, 4-h daytime, and 4-h nighttime periods (including natural log–transformed [ln] root mean square of successive RR interval differences [RMSSD], ln absolute power of the high-frequency band [0.15-0.4 Hz] [HF], ln absolute power of the low-frequency band [0.04-0.15 Hz], and LF-to-HF ratio [LF/HF]) were then assessed in the 2 groups. Spearman correlation analysis was used to assess the correlation between total burden of CSVD and HRV parameters. HRV parameters with P value <0.05 in correlation analysis were included in the multivariable logistic regression analysis, and restricted cubic spline analysis was performed to assess dose-response relationships. Results: Daytime 4-h lnRMSSD (r = –0.221; P = 0.008) and 4-h lnHF (r = –0.232; P = 0.005) were negatively correlated with total burden of CSVD, and daytime 4-h lnLF/HF (r = 0.187; P = 0.025) was positively correlated with total burden of CSVD. There was no correlation between nighttime HRV parameters and total burden of CSVD. After adjustments were made for potential confounders, daytime 4-h lnRMSSD (OR = 0.34; 95% CI: 0.16-0.76), 4-h lnHF (OR = 0.57; 95% CI: 0.39-0.84), and 4-h lnLF/HF (OR = 2.12; 95% CI: 1.18-3.82) were independent predictors of total burden of CSVD (all P <0.05). S-shaped linear associations with moderate-to-severe total burden of CSVD were seen for daytime 4h-lnRMSSD (P for nonlinearity = 0.543), 4-h lnHF (P for nonlinearity = 0.31), and 4-h lnLF/HF (P for nonlinearity = 0.502). Conclusion: Daytime parasympathetic HRV parameters are independent influencing factors of total burden of CSVD and may serve as potential therapeutic observation indicators for CSVD.